Indonesian teachers practices of supporting self-regulated learning in the ESP grammar - Nina Inayati; Ria Arista Asih (Studies in English Language and Education, 2025)
Despite the rich literature on learners self-regulated learning (SRL), limited studies were conducted on teachers support for learners autonomy in language learning, especially in grammar instruction in teaching English for specific purposes (ESP). Framed using Zimmerman and Campillos (2003) SRL framework, this study explores English teachers support to learners cyclical and triadic phases during grammar courses. Two ESP instructors were purposely chosen as the focus of the study, and rich data were collected through observation, interview, and document analysis. Reflexive thematic analysis (RTA) was employed to analyse the data. The findings suggest that despite autonomy and SRL not being prioritised in the curriculum, the teachers showed extensive support for students SRL through instructional designs and classroom practices. One teacher preferred to focus more on motivation raising with ample environmental support, while the other emphasised observation of learning with rich behavioural support. Both teachers also employed gamified learning via digital platforms to support students' learning beyond the classroom. They also tend to lean more toward the cyclical phases than the triadic phases in their support for SRL. These findings shed some light on the urgently needed understanding of language teachers cognition and practices in supporting learners SRL; thus, relevant pedagogical and research implications were offered.